"Is Women's Freedom a Myth or Reality"? The Context of Working Class Women in Bangladesh (Global Journal of Human-Social Science, 2020)
Lately, women's freedom is the most uttered concept in Bangladesh. Civil society has given the statement that women are onward to freedom. Women are now taking part in the various outside world. They are crushing their boundary of the household. But It was confusing after hearing those words. Is there any word called women's freedom? Civil society has given its arguments based on women's economic freedom to earn money. The question has arisen on that issue. If it is so, women are getting freedom as they are working outside and attaining economic solvency. Then what about working-class women who are working in the garments factory. Why are they deprived of equal wages in their workplace? Why are they harassed by the office staff and the male counterparts? Why are they being exploited in the household? Why are their voices not heard? Are there any answers to these questions? Working class women are being exploited in their households as they belong to the patriarchal society. Capitalism is using them as they are cheap labor.
Keywords: women’s freedom; economic freedom; working-class women; patriarchal society